Structure and aspects of amorphous detonating covers are based on iron - Artemchuk, V. V. (Science and Transport Progress, 2011)
The structure and properties of the stratified amorphous coatings obtained in the conditions of thermal spraying are considered in the article. The comparative analysis of coatings from iron-based alloys is presented. The factors influencing the formation of amorphous structure in detonation coatings from metallic alloys are shown. The influence of structure of coatings upon the wear resistance and endurance of the recovered details is experimentally shown.